The royal secret - Taylor, Andrew, 1951 October 14- (HarperCollinsPublishers, 2021)
While James Marwood investigates a colleague's murder, which brings unexpected dangers, architect Cat Hakesby designs a Poultry House for the woman that the King loves most in the world, but unbeknownst to them an explosive royal secret could rip England apart.